PENERAPAN METODE LATIHAN OLAH VOKAL TERHADAP KETERAMPILAN BERNYANYI ANAK TUNANETRA SMALB - nurilawati, riski (Jurnal Pendidikan Khusus, 2015)
ABSTRACT Each person, blind people also, have certain potential which able to developed as their life skill, one of it was singing skill.  For developing that skill we used appropriate method, it was vocal practicing. The purpose of this research was to know the implementation of vocal practicing method toward blind student’s singing skill at SMALB-A YPAB Surabaya. This research was use quantitative approach, pre eksperimental researche with one group pre test-post test design.  A number of students grades XI was involved in this research. Data was collect by test method and use sign test nonparametric statistic analysis. Based on pre test-post test  data analysis it obtained positive change. Mean score on pre test was 49.998, and rised 82.224, after given intervention  during 8 meeting. Research data showed n=5, with X= 4,5, = 5% (0,05),  and µ = 2,5 which analysed by sign test method. Then,  Z count was (Zh) = 1.79 and compared with two side sign test 1.64, so Zh > Z tabel, it was 1.79 > 1.64 which interpreted that, there was effect of vocal practicing method toward blind student’s singing skill  in SMALB-A YPAB Surabaya.    Key Word : singing skill, vocal practicing method.